(untitled) (Research, Society and Development, 2022)
Objective: to present and describe the result of cross-hormonal therapy in a transsexual woman treated at a specialized center in the State of Rio de Janeiro. Methodology: A case study carried out from June 2022 onwards, with a transsexual individual treated at the single-gender identity outpatient clinic of a public health institution, which performs multidisciplinary follow-up of cross hormone therapy. Results: The elderly transsexual has risk behaviors, health risk use and quality of life. The user possibly presented several comorbidities, but there is no way to categorically state the relationship with its use or self-medication, as the aging process also contributes to the development of diseases. Final considerations: You must accompany the consultations, collaborating with your expertise, in the early detection of diseases and estimates that should evaluate the hormonalization process. They should also promote and encourage habits in order to minimize the increase in aging and therapy changes, as well as improve their quality of life.